METODE VALUASI MANAKAH YANG LEBIH TEPAT UNTUK MERGER DAN AKUISISI? - Johan, Suwinto; Herbani, Laura (Jurnal Muara Ilmu Ekonomi dan Bisnis, 2018)
The aim of this research is to study the various valuation methods in merger and acquisition transaction. Valuation is the most important part of a merger and acquisition deal. The seller always expects the highest value, however the buyer will expect to have a reasonable value of the target. It is important both parties agree and understand the basic views. The research will be focused on the most important variables and the valuation process of each method. The research will provide advantages and disadvantages of each method. The research also stated 3 important points in valuation, which are scarcity, regulation and time of valuation.Kata Kunci : Akuisisi, Merger, Nilai Perusahaan, Valuasi JEL Clarification Code : G32, G33, G34